Endogenous opioids mediate basal hedonic tone independent of dopamine d-1 or d-2 receptor activation - Narayanan, S. (2004)
Exogenously administered opiates are recognized as rewarding and the involvement of dopamine systems in mediating their apparent pleasurable effects is contentious. The aversive response to naloxone administration observed in animal studies suggests the presence of an endogenous opioid tone regulating hedonic state. We sought evidence for the requirement for dopamine systems in mediating this action of endogenous opioids by determining whether mice deficient in dopamine D-1 or D-2 receptors were able to display conditioned place aversion to naloxone. Mice received saline in the morning in one chamber and either saline or naloxone (10 mg/kg, s.c.) in the afternoon in another chamber, each day for 3 days. On the test day they were given free access to the testing chambers in the afternoon. Similar to their wild-type littermates, D-1 and D-2 receptor knockout mice receiving naloxone in the afternoon spent significantly less time on the test day in the compartment in which they previously received naloxone, compared with animals receiving saline in the afternoon. The persistence of naloxone-conditioned place aversion in D-1 and D-2 knockout mice suggests that endogenous opioid peptides maintain a basal level of positive affect that is not dependent on downstream activation of dopamine systems involving D-1 or D-2 receptors.